Audit committee practice in the polish listed stock companies. Present situation and development perspectives - Szczepankowski, Piotr (Business, Management and Economics Engineering, 2012)
The audit committee is one of the parts of corporate governance mechanism, which is understood as the relationship between corporate managers, directors and the providers of equity, people and institutions who save and invest their capital to earn the return. This study presents survey research results of audit committee activity in Polish public stock companies quoted on the Warsaw Stock Exchange (WSE). The purpose of this paper is to present the audit committee practice in Poland after 2009. The paper shows that the audit committee practice is still the most problematic issue of transitional Polish corporate governance rules. The survey has shown that the corporate needs and its implementation, and communication with listed companies leave a lot of room for improvement. The paper is based on the documents prepared in 2010 by PricewaterhouseCoopers, the Polish Association of Listed Companies and the Polish Institute of Directors.